The Influence of Lazada's Jingle Towards Purchase Intention with Brand Awareness as the Mediating Variable - Halim, Angeline; Qastharin, Annisa Rahmani (Integrasi Sains Media, 2024)
In today's digital era, e-commerce has gained significant popularity among Indonesian consumers. Lazada, a leading e-commerce platform in Indonesia, employs various advertising strategies, including the use of a catchy jingle, to enhance brand awareness and drive purchase intention. This study examines the effectiveness of Lazada's jingle in increasing customer purchase intention. Advertising effectiveness measures how well the campaign has achieved its goals, specifically in increasing purchase intention in this research. Despite widespread exposure of Lazada's jingle across various platforms, public reactions are mixed; some consumers find the jingle entertaining and memorable, while others consider it annoying and intrusive. This research aims to determine whether the jingle effectively enhances brand awareness and if this increased awareness translates into higher purchase intention. The study investigates the influence of Lazada's jingle on consumers' purchase intention, with brand awareness serving as a mediating variable. It focuses on Generation Z and Millennials aged 17 to 42 in Indonesia, as they represent a significant portion of Lazada's target market. Data were collected using a quantitative approach through preliminary and main research involving 409 respondents via online survey questionnaires. The findings reveal that Lazada's jingle significantly enhances brand awareness, which in turn positively influences purchase intention. The study highlights the importance of incorporating catchy jingles into advertising strategies to boost brand awareness and consumer engagement. These insights are crucial for e-commerce marketers aiming to optimize their advertising efforts and improve customer retention, thereby validating and strengthening existing studies. Future research should explore the long-term effects of jingles on consumer behavior and emotional response, as well as the frequency with which the jingle is played.